Corporate initiatives of the clergy of Tobolsk diocese in the field of financial security of the clergy in the last quarter of the 19th — early 20th centuries - Alexander Kruglikov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with the initiatives of the clergy of the Tobolsk diocese in the issue of material provision of clergy and clergymen in the last quarter of the XIX - early XX centuries. The article characterizes the clergy in the context of the socio-economic status of clerics, based on the regional material. It shows the transition from institutional to corporate method of material provision of the clergy due to the critical attitude of the clergy to the reforms of the pension system, as well as the process of formation of new forms of non-state pension provision among the clergy. For the first time on the basis of the material presented in Tobolsk diocesan bulletins the evolution of the statute of the mutual aid fund of the clergy of the Tobolsk diocese, as well as the factors that influenced its changes and additions were traced. It is shown that in the process of administration of the new diocesan structure there were issues that were not spelled out in the first draft of the fund, which did not provide for all cases of issuing a lump-sum allowance, return of membership fees to the participants of the fund and the issuance of refundable loans and required immediate consideration. On the basis of the reports of the Mutual Aid Fund of the clergy of the Tobolsk diocese the cash flow, the issuance of lump-sum allowances and loans of the Mutual Aid Fund of the clergy of the Tobolsk diocese in 1894-1914 are traced. The author comes to the conclusion that the evaluation of the activities of the mutual aid fund of the clergy of the Tobolsk diocese can not be considered only through the prism of the received lump sum benefits and loans. In spite of the fact that the main task of the fund was not achieved - the transformation into an emeritus fund, and the clergy did not receive non-state pensions, it was possible to achieve a positive impact on the material situation of the clergy, who were in extremely difficult financial situation.